Religion and Responsibility-Taking Among Offenders in Colombia and South Africa: A Qualitative Assessment of a Faith-Based Program in Prison - Anderson, Matthew Lee (International journal of offender therapy and comparative criminology, 2023)
This paper examines whether religion contributes to offenders taking responsibility for crimes. Specifically, we assessed whether participation in The Prisoner’s Journey (TPJ), a bible study program, increased or decreased responsibility-taking. We also examined whether religious offenders that did not participate in TPJ were likely to take responsibility for their offenses. For this study, we conducted a quasi-experiment in two Colombian and five South African prisons from 2018 to 2019, collecting data from personal interviews with a total of 73 inmates—42 TPJ participants and 31 non-participants—before and after the program. Offenders frequently offered subtle accounts of responsibility that incorporated their own agency with other factors. Highly religious offenders were equally likely to take responsibility, and in some cases participation in TPJ heightened responsibility. In sum, this paper presents evidence that religious beliefs and practice are commensurate with responsibility-taking and desistance from crime.